ANALISIS NILAI PENDIDIKAN DALAM NOVEL “HABIBIE & AINUN” KARYA B.J HABIBIE - Risma Herawati; Andri Andri; Yusep Ahmadi F (IKIP Siliwangi, 2019)
The making of this article aims to examine and know the values that educate after reading the novel